The agency costs of family ownership: Evidence from innovation performance - Chi, Yung-Ling (Journal of Banking & Finance, 2023)
The paper examines how controlling ownership by a family group affects a firm’s innovation by exploiting the unique disclosure regime of Taiwanese public firms that reflects the genealogy of the controlling family. A causal relationship is identified using the number of the CEO’s siblings as an instrumental variable for ownership collectively held by the controlling family. The findings suggest that agency costs generated by family ownership dominate the benefit of the social capital attached to the family group. Evidence shows that agency costs are attributable to excess control rights rather than to conflicting family and business objectives. However, the negative impact on innovation is mitigated when external governance from large shareholders is present and when high financing costs are expected. The study disentangles the various factors generating agency costs and sheds light on how the distribution of corporate control shapes innovation performance.